2022
DOI: 10.3390/su142416708
|View full text |Cite
|
Sign up to set email alerts
|

Shuttle Bus Timetable Adjustment in Response to Behind-Schedule Commuter Railway Disturbance

Abstract: Shuttle bus connection is a valid technique to handle unplanned problems and promote sustainable transportation. The study describes tools that facilitate the shuttle bus timetable adjustment responding to a disturbance resulting from behind-schedule trains on a commuter railway. This behind-schedule disturbance is divided in four stages allowing for different delay ranges. The problem and its solution involve different elements, such as shuttle bus route selection, stop location, and timetable adjustment. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The above studies illustrate that improving the capacity of public transport can effectively increase the share of public transport passengers and that a combination of rail and regular buses can effectively improve urban connectivity and accessibility. From the perspective of the travelers' transfer experience, Feng et al [18] proposed a non-linear integer planning model that substantially reduces the cost of waiting time for rail travelers to switch to buses. By optimizing rail and bus schedules, Kang et al [19] showed that improving schedule synchronization can effectively improve traveler service.…”
mentioning
confidence: 99%
“…The above studies illustrate that improving the capacity of public transport can effectively increase the share of public transport passengers and that a combination of rail and regular buses can effectively improve urban connectivity and accessibility. From the perspective of the travelers' transfer experience, Feng et al [18] proposed a non-linear integer planning model that substantially reduces the cost of waiting time for rail travelers to switch to buses. By optimizing rail and bus schedules, Kang et al [19] showed that improving schedule synchronization can effectively improve traveler service.…”
mentioning
confidence: 99%